Human-Centred Artificial Intelligence in Progressive Education : Unravelling the Benefits and Challenges in Qatar’s HEIs - Jansen, Bernard J.; Jung, Soon-gyo; Farooq, Ali; Salminen, Joni; Aldous, Kholoud; Msefula, Pilira Stella; Alabed, Amani; Khan, Salar M.; O’Kennedy, Richard (My University, 2025)
Algorithmically generated personas (AGPs) can provide actionable insights into the needs, preferences, and behaviours of stakeholders, including Applicants, Students, Alumni, Faculty, and Staff (ASAFS) for progressive education at higher education institutes (HEIs) in Qatar. AGPs empower data-based decision-making, and contribute to progressive education by representing stakeholders in an empathic format. This chapter sheds light on the pivotal role of alumni, showing how the innovative approach of using personas enables the “beyond education” concept, while providing strategic foresight for HEIs in Qatar. Machine learning models can generate AGPs as humanised representations of these key stakeholders. Building on our multi-year experience in studying AGPs, we argue that these personas can significantly aid HEI decision-makers in designing more learner-centred and inclusive curricula, pedagogy, and assessment via empathic understanding. While AGPs have been prevalent in marketing or design, their potential remains largely unexplored in HEIs.
Keywords: fi=Markkinointi|en=Marketing|